The Impact of Autocratic, Democratic, and Laissez-faire Leadership Styles on Employee Motivation “An Analytical Study at Several Directorates within the Ministry of Interior in the Soran Independent Administration” - Hamze, Murad; Sadiq , Sabir (Journal of Economics and Administrative Sciences, 2025)
This study examines how autocratic, democratic and laissez-faire styles of leadership affect employee motivation in the different directorates of the Ministry of Interior, otherwise known as Soran Independent Administration. Research has proven that such styles of leadership are going to affect the way employees engaged and committed themselves to the performance outcome for the sake of organizational success. High levels of democratic leadership or participative decision-making and inclusivity-related structures would, however, create conditions conducive to employee motivation. Recommendations for further research have been made in relation to the study variables. An additional area for further development includes the relationship between laissez-faire, leadership and employee motivation, especially pertaining to the more experienced employees. An autocratic style of leadership is associated with highly centralized decision-making and closely controlled decision environments. In this context, the style may portray itself as very little or even null in terms of motivational influence on employees. This negative emphasis often goes along with lowered creativity and less engagement by the employees with work. These findings indicate the need for anchoring leadership styles under a banner of a scope that should create the entire base of guidelines on open communication trust and employee empowerment as a more strategic approach to better employee motivation and improved organizational outputs. Indeed, by applying participative and autonomous leadership approaches to organizations, such factors become important in creating an environment really conducive to innovation, loyalty, and productivity. Its outcomes point out leadership strategies that can be optimized for effective employee motivation and remind organizations about the practical ways to move toward developmental success.